2019
DOI: 10.1039/c9ce01008d
|View full text |Cite
|
Sign up to set email alerts
|

Halobenzyl alcohols as structurally simple organogelators

Abstract: We report 11 simple halobenzyl alcohols, each comprising of only 16 atoms, as organogelators for aliphatic hydrocarbon solvents. Their self-assembly is similar in both gel and crystal states and involve OH⋯O, CH⋯O, CH⋯π, O⋯X, CH⋯X and X⋯X interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…In some cases, gelator has a similar mode of packing in crystal and gel state by comparing the powder X ray diffraction (PXRD) patterns of crystals and xerogels. If these patterns match well, the crystal structure can be used to understand the molecular assembly in the gel [32,44,56–58] . Such strategy cannot be used in the absence of single crystals of the gelator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, gelator has a similar mode of packing in crystal and gel state by comparing the powder X ray diffraction (PXRD) patterns of crystals and xerogels. If these patterns match well, the crystal structure can be used to understand the molecular assembly in the gel [32,44,56–58] . Such strategy cannot be used in the absence of single crystals of the gelator.…”
Section: Discussionmentioning
confidence: 99%
“…In single‐component systems, the introduction of halogen has a significant effect on the self‐assembly of low‐molecular‐weight gelators in organic solvents or in polar water, proving to be a promising strategy for effective regulation of gels properties. The reason could be explained by two main aspects [31–33] . The electron absorption properties and heavy atom effect of halogen substituents are beneficial to enhance the intermolecular interaction of halogenated compounds.…”
Section: Halogen Bonding In Low‐molecular‐weight Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structures and properties of liquids containing alcohols and their H-bonding interactions have been of interest in many laboratories. Among various alcohols, tert -butyl alcohol ( t -BuOH) has received much attention. Relative to some other aliphatic alcohols such as methanol and ethanol, t -BuOH forms smaller H-bonded aggregates due to its special geometric shape and stronger hydrophobic character . Yonker et al found that the H-bonding aggregates in tertiary alcohols in general, and particularly in t -BuOH, are mainly cyclic.…”
Section: Introductionmentioning
confidence: 99%